Investigating the Rural and Entrepreneurial Development through Microfinance - Parray, Zahoor Ahmad; Rather, Raouf Ahmad Ahmad; Bhat, Shabir Ahmad; Ahmad, Pirzada Sajad (Universitas Prasetiya Mulya, 2022)
Microfinance has been evolving to be a decisive factor in poverty reduction, rural and entrepreneurial development. This research aims to find out the impact of microfinance on rural/socio-economic development and entrepreneurial skill development. Particularly, this study attempts to explore the impact of microfinance on social development, financial empowerment, education, healthcare, economic independence, and entrepreneurial development. Data was collected through questionnaires taken from the beneficiaries of the National Rural Livelihood Mission (NRLM) erstwhile Swaran Jayanti Shahri Rozgar Yojana (SJSRY) microfinance scheme in the Union Territory of Jammu and Kashmir, India. A purposive sampling method, exploratory factor analysis, and paired sample t-test were used in this study. The findings prove that microfinance facilitates social development, improved financial empowerment, and promotes decision-making relating to education and healthcare among beneficiaries. The finding also indicates that microfinance helps to increase entrepreneurial skill development among the beneficiaries. This study offers an insight how microfinance eliminates poverty and facilitates social development as well as entrepreneurial skills. These findings have essential implications for academics, policymakers, and microfinance institutions.